A NEW APPROACH TO CALCULATING THE DIFFERENCE BETWEEN TWO NATURAL NUMBERS - Robson Barros, Antonio (Journal of Interdisciplinary Debates, 2024)
This paper aims to present a way to calculate the difference between two natural numbers in which the digits of the minuend are almost or all smaller than the digits of the subtrahend, without using the archaic expression “x to y”, as in the example 23 - 19 where we say “nine to thirteen is four, go one”, which the student has great difficulty understanding. Therefore, this text contributes positively to the teaching-learning process of the aforementioned content.